State Image of Mongolia: Between National Identity and Globalization - S. A. Semedov; V. A. Sukhareva (Концепт: философия, религия, культура, 2021)
The article studies the construction of the state image of Mongolia and its peculiarities. Mongolia is a country undergoing social and cultural transformation that includes reevaluation of image strategies. State image is an international statement based on highlighting one’s original characteristics that make a country attractive to investors and international partners. At the same time, it should reflect real cultural practices and allow for advancing national interests. The present study deploys the methodology of case study, SWOT analysis, thematic analysis of connotations that form the external and internal image of Mongolia. The purpose of this article is to investigate the strategies of image construction in today’s Mongolia. The article is aimed to give a semantic vision of the external image of Mongolia by identifying the most common words and expressions that are used in media to describe modern Mongolia. The second objective was to lay out the problematic aspects of creating an image of Mongolia as a promising and growing country despite the fact that now it goes through a challenging period of its history. The third objective is to investigate the ways Mongolia attempts to address these problems. For this purpose, the authors analyze government programs set to form and establish a modern image of Mongolia. These programs include a variety of documents, such as the National Program for the Promotion of Mongolia Abroad and others. Another line of research included the analysis of the work on the inclusion of Mongolian natural and cultural heritage on the list of UNESCO World Heritage Sites. The novelty of the research comes from a unique perspective on the construction of state image of Mongolia as an ethnic and cultural brand from the point of view of marketing strategies. The authors conclude that building brand and image of Mongolia is based on the civilizational approach. This approach to re-evaluating and re-creating Mongolia’s image leads to combining opposite characteristics. The country is presented as both ancient and modern, traditional and responsive to change. Such combination of controversial aspects makes allows for implementing archaic elements into the discourse of the catch-up modernization resulting in a positive state image. Mongolia’s experience in making a new image shows the potential of equating national and ethnocultural identity.